Summary of Clinical Experiences With Tamsulosin for the Treatment of Benign Prostatic Hyperplasia - Lowe, Franklin C (MedReviews, LLC, 2005)
Tamsulosin, a uroselective α(1A)-adrenergic-receptor antagonist, has been shown to improve lower urinary tract symptoms associated with benign prostatic hyperplasia. It has a better side effect profile than earlier α-adrenergic-receptor antagonists, which were initially developed as antihypertensive agents. Clinical trials of 1 year or longer with tamsulosin show high tolerability for the 0.4 mg dose and no significant interaction with other antihypertensive medications.